Analisis Faktor Resiko Filariasis Di Wilayah Kerja Puskesmas Ngemplak Kabupaten Boyolali Jawa Tengah - Athanasia Budi Astuti; Sri Mulyanti (Poltekkes Kemenkes Surakarta, 2019)
Background: Currently filariasis is one of the priority diseases to be eliminated. WHO in 2000 declared the Global Goal of the Elimination of Lymphatic Filariasis as a Public Health Problem by the Year 2020. The Indonesian government's policy is to gradually implement Filariasis Elimination Program through Filariasis Provision of Mass Drug Prevention (POPM) programs in filariasis-endemic districts/cities and management of filariasis clinical cases. Filariasis cases in Central Java in 2013 - 2016 tended to increase, including in Boyolali Regency. If this condition is not immediately treated properly, it can make it possible to end up with filariasis. Methods: Materials and methods. This research is a survey research with mixed-research or mixed research approach. Respondents were patients and families of filariasis sufferers, government stakeholders, and health stakeholders. Data were obtained through in-depth interviews, focus group discussions, and field observations. Results: Filariasis risk factors found were (1) lack of knowledge of patients and families about the treatment and prevention of transmission of filariasis (2) mosquito vector control has not been done well (3) Home environment conditions (3) Still found gaps or gaps between health sector stakeholders (4) There are still filariasis patients who have not carried out filariasis treatment properly. Conclusion: Risk factors for filariasis are individual factors, lack of efforts to control mosquito vectors, environmental factors, and the existence of gaps between health stakeholders.